2016
DOI: 10.1093/europace/euw093
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ischaemic stroke on atrial fibrillation-related healthcare cost: a systematic review

Abstract: The aim of this study was to summarize healthcare costs incurred by patients with atrial fibrillation (AF) who developed ischaemic stroke, explore factors associated with increased cost, and highlight the importance of anticoagulation therapy for stroke prophylaxis. A systematic literature search of PubMed, EMBASE, Web of Science, and the health economic evaluation database was conducted up to December 2015. Studies focused on the cost and/or resource utilization of ischaemic stroke in patients with AF were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 51 publications
1
24
0
4
Order By: Relevance
“…In 25 465 US NVAF patients studied between 1999 and 2009, the most significant costs of first ischaemic stroke/major bleeding occurred in the first year, but total healthcare costs remained elevated up to 3 years post‐event 21 . The considerable economic burden of ischaemic stroke in AF patients was also highlighted in a systematic review including 16 studies of ischaemic stroke costs and HRU in patients with AF across nine countries 22 . In agreement with our results, the major component of overall costs was hospitalization.…”
Section: Discussionmentioning
confidence: 96%
“…In 25 465 US NVAF patients studied between 1999 and 2009, the most significant costs of first ischaemic stroke/major bleeding occurred in the first year, but total healthcare costs remained elevated up to 3 years post‐event 21 . The considerable economic burden of ischaemic stroke in AF patients was also highlighted in a systematic review including 16 studies of ischaemic stroke costs and HRU in patients with AF across nine countries 22 . In agreement with our results, the major component of overall costs was hospitalization.…”
Section: Discussionmentioning
confidence: 96%
“…Atrial fibrillation (AF) is the most common clinical arrhythmia and is the leading cause of disabling stroke ( 1 ). As the prevalence of AF is increasing due to an aging population ( 2 ), AF exerts an increasing strain on the health care system ( 2 , 3 ). Current management of AF focuses on both medical and catheter ablation–directed strategies ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even though several studies have analyzed costs for AF-related ischemic strokes, a lot of disparities are present in their methodologies, especially regarding cost calculation [25], resulting in unavoidable obstacles in making accurate comparisons. To our knowledge, only Sussman et al (United States) [8], Wang et al (United States) [26], and Ali et al (United Kingdom) [27] reported the costs for IS stratified by AF.…”
Section: Introductionmentioning
confidence: 99%